THE IMPACT OF NEURO-LINGUISTIC PROGRAMMING ON ENGLISH LANGUAGE ACQUISITION - Xalilova Ruxsora Inatullo qizi; Zubaydova Nilufar Nematullayevna; Saloxiddinov Manuchehr (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Language acquisition is a complex cognitive process influenced by numerous psychological, social, and neurological factors. One of the methodologies that has gained attention in this realm is Neuro-Linguistic Programming (NLP), a psychological approach that explores the connection between language, behavior, and cognitive patterns. While NLP has been widely used in therapy and personal development, its application in English language acquisition remains a debated topic. This article critically examines the impact of NLP on learning English, comparing its effects on young learners and adults, and assessing its effectiveness with empirical insights